MEDIA SOSIAL DAN CITRA DESTINASI UNTUK KEBERLANJUTAN WISATA ALAM KAWASAN HUTAN RESORT SITUGUNUNG - Setiadi, Sandi; Sarah Ginanjar, Noornissa (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
The purpose of this study was to analyze and evaluate the influence of social media on sustainability and the influence of destination image on the sustainability of natural tourism in the Situgunung Sukabumi Resort Forest Area, West Java. The type of research uses a quantitative method, with a type of associative causality relationship. For the number of samples in this study as many as 140 respondents using non-stochastic techniques, with the number of samples used in this study calculated using the Hair formula. In this study, data analysis was measured and tested using the Structural Equation Model (SEM) method and processed with SmartPLS3 software. The results of the study are that there is a positive and significant influence between social media on sustainability and there is a positive and significant influence between destination image on sustainability.